Characteristics of beef traits in crossbred bulls with different degrees of its marbling - O. Kruk; A. Ugnivenko (Тваринництво та технології харчових продуктів)
The purpose of this experimental study was to characterise the quantitative and qualitative traits of beef in the most common domestic animals in Ukraine from Ukrainian Black-and-White dairy and Holstein cattle bulls at different classes of marbling severity of m. longissimus dorsi. Twenty-six carcasses from 20-22-month-old bulls of the farm “Zhuravushka” located in Brovary district of Kyiv region, Ukraine, served as material for the study. The marbling of m. longissimus dorsi was evaluated according to the JMGA standard (2000) and the morphological composition and quality characteristics of the carcasses were determined. The obtained results showed that in the medium and good (3 to 5 points) class of marbling, the marbling of the m. longissimus dorsi in carcasses was higher than in the unsatisfactory and below average grade (1 and 2 points), the content of muscle tissue of the second grade was 6.5 points (P ≤ 0.01), bone – 2.5 points (P ≤ 0.01), and the carcass conformation (meatiness) was better developed by 33.3% (P ≤ 0.01), the development of its cover with adipose tissue – by 31.8% (P ≤ 0.05) and muscle colour – by 10.2% (P ≤ 0.05). At the highest (from 3 to 5 points) class of marbling of beef, the content of muscle tissue of the highest (3.9 points) and first (2.6 points) grades was significantly (P ≤ 0.05) lower, and the size of the “muscle eye” area was 22.5% lower (the difference was not statistically significant). Accounting for the probable difference in slaughter signs depending on the marbling of beef, the data obtained can be used to predict the content of certain grades and quality characteristics of muscle tissue in carcasses of crossbred bulls from Ukrainian Black-and-White and Holstein dairy cattle